Abyssal macrofauna of the Kuril–Kamchatka Trench area (Northwest Pacific) collected by means of a camera–epibenthic sledge. (January 2015) - Brandt, A.; Elsner, N.O.; Malyutina, M.V.; Brenke, N.; Golovan, O.A.; Lavrenteva, A.V.; Riehl, T.
Abstract: Abyssal macrofaunal composition of 21 epibenthic sledge hauls from twelve stations taken in the Kuril–Kamchatka Trench (KKT) and at the adjacent abyssal plain, Northwest Pacific, is presented. Sampling with the fine meshed epibenthic sledge yielded higher abundances and species richness than was reported from previous expeditions from board of RV Vityaz . In total 84, 651 invertebrates were sampled with RV Sonne between July and September of 2012 (31, 854 invertebrates if standardised for 1000 m 2 trawled distances) from 41 taxa of different taxonomic ranks (15 phyla, 28 classes, 7 orders) were sampled from a trawled area of 53, 708 m² and have been analyzed. Few taxa were frequent and most taxa were rare in the samples, twelve taxa occurred with more than 1% frequency. Of these, the Polychaeta were most abundant followed by the benthic Copepoda and Isopoda. Total numbers of individuals varied between stations and were highest with 4238 individuals at station 2-10 close to the KKT in 4865 m depth and lowest with 374 individuals at station 6-11 in 5305 m depth. At this station also the lowest number of taxa occurred (18 taxa) while the highest number occurred with 31 taxa at station 3-9 in 4991 m depth. Numbers of individuals decreased with increasing depth between 4830 and 5780 m. Crustaceans of the superorder Peracarida were one of the dominating taxa with four orders occurring frequently in most samples. In total, Isopoda were most important and occurred with 59% of all peracarid orders sampled, followed by Amphipoda with 21%, Tanaidacea with 11%, Cumacea with 9%, and Mysidacea with <1%. The communities of the stations (and hauls) of the KKT abyssal area differ in terms of taxon composition from each other. A cluster analysis (nMDS) performed for all sampled stations revealed no clear pattern of community similarity between stations or hauls. All hauls close to the trench (2-9 and 2-10 close to the eastern slope of the KKT; and 3-9 and 4-3 at the western slope) were most different to the other hauls. Hauls 8-9 and 8-12 as well as 5-10 and 7-10 in the approximate centre of the overall research area were most similar (88% similarity). The non-isolated KKT area is characterized by higher abundances and higher benthic species richness than the geographically isolated and young deep-sea basin of the Sea of Japan.